Recent advances in the management of AL Amyloidosis - Kastritis, Efstathios; Dimopoulos, Meletios A. (British journal of haematology, 2016)
Summary Immunoglobulin light chain (AL) amyloidosis, the most common of the systemic amyloidosis, is characterized by the deposition of amyloid fibrils that derive from the aggregation of misfolded monoclonal immunoglobulin light chains. Amyloid fibrils disrupt tissue architecture and the pre‐fibril oligomers are directly toxic to myocardiac cells, causing cardiac dysfunction. The lethal consequences of AL amyloidosis are due to the toxic product and not due to the malignant behaviour of the plasma cell clone; however, the characteristics of this clone are associated with long‐term prognosis. Early and accurate diagnosis is the key to effective management, but is challenging. Modern chemotherapy options (including autologous transplantation, bortezomib, lenalidomide) have improved the outcomes of patients at low or intermediate risk, but the prognosis of patients with severe cardiac dysfunction is still poor. Therapies targeting amyloid deposits and the amyloidogenic process are under investigation and offer promise for better future treatments.